Posted by jnky on Tuesday, March 18, 2014 at 11:39pm.
- derivatives - Reiny, Wednesday, March 19, 2014 at 12:00am
I assume that you want the derivative, since you titles your post that way.
if y = x^2cosx-2xsinx-2cosx
dy/dx = (x^2)(-sinx) + 2x cosx - 2x(-cosx) - 2sinx + 2sinx
= -x^2( sinx) + 4x( cosx)
etc if needed
- derivatives - oops - Steve, Wednesday, March 19, 2014 at 5:53am
d/dx sinx = cosx
- derivatives - Reiny, Wednesday, March 19, 2014 at 7:36am
sloppiness on my part
Answer this Question
More Related Questions
- Math - Solving for Trig Equations - For the following equation, why cannot I not...
- Math - Find the limit of (2cosx+3cosx-2)/(2cosx-1)as x tends to pi/3.
- Pre Calculus - Having trouble verifying this identity... cscxtanx + secx= 2cosx ...
- trig - prove that (2cosx+1)(2cosx-1)= 1 +2cos2x
- math - tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx ...
- Calculus - Determine the concavity and find the points of inflection. y=2cosx + ...
- RESPONSE to PreCalc Question - h t t p : / / w w w . j i s k h a . c o m / d i s...
- Maths Calculus Derivatives & Limits - Using the definition of the derivative ...
- Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...
- trigonometry - solve: 2cosx-1=0